Cleavable Crosslinkers as Tissue Fixation Reagents for Proteomic Analysis. (16th February 2018) - Ongay, Sara; Langelaar‐Makkinje, Miriam; Stoop, Marcel P.; Liu, Nora; Overkleeft, Hermen; Luider, Theo M.; Groothuis, Geny M. M.; Bischoff, Rainer
Abstract: Formaldehyde fixation is widely used for long‐term maintenance of tissue. However, due to formaldehyde‐induced crosslinks, fixed tissue proteins are difficult to extract, which hampers mass spectrometry (MS) proteomic analyses. Recent years have seen the use of different combinations of high temperature and solubilizing agents (usually derived from antigen retrieval techniques) to unravel formaldehyde‐fixed paraffin‐embedded tissue proteomes. However, to achieve protein extraction yields similar to those of fresh‐frozen tissue, high‐temperature heating is necessary. Such harsh extraction conditions can affect sensitive amino acids and post‐translational modifications, resulting in the loss of important information, while still not resulting in protein yields comparable to those of fresh‐frozen tissue. Herein, the objective is to evaluate cleavable protein crosslinkers as fixatives that allow tissue preservation and efficient protein extraction from fixed tissue for MS proteomics under mild conditions. With this goal in mind, disuccinimidyl tartrate (DST) and dithiobis(succinimidylpropionate) (DSP) are investigated as cleavable fixating reagents. These compounds crosslink proteins by reacting with amino groups, leading to amide bond formation, and can be cleaved with sodium metaperiodate ( cis ‐diols, DST) or reducing agents (disulfide bonds, DSP), respectively. Results show that cleavable protein crosslinking with DST and DSP allows tissue fixation with morphology preservation comparable to that of formaldehyde. In addition, cleavage of DSP improves protein recovery from fixed tissue by a factor of 18 and increases the number of identified proteins by approximately 20 % under mild extraction conditions compared with those of formaldehyde‐fixed paraffin‐embedded tissue. A major advantage of DSP is the introduction of well‐defined protein modifications that can be taken into account during database searching. In contrast to DSP fixation, DST fixation followed by cleavage with sodium metaperiodate, although effective, results in side reactions that prevent effective protein extraction and interfere with protein identification. Protein crosslinkers that can be cleaved under mild conditions and result in defined modifications, such as DSP, are thus viable alternatives to formaldehyde as tissue fixatives to facilitate protein analysis from paraffin‐embedded, fixed tissue. Abstract : Reversible protection : Due to formaldehyde‐induced crosslinks, fixed‐tissue proteins are difficult to extract, which hampers MS proteomic analyses. Alternatively, tissue fixatives based on reversible crosslinkers result in a 20‐fold higher protein extraction yield under mild conditions and a significantly improved protein identification rate.